Perancangan Enterprise Architecture Menggunakan TOGAF ADM untuk Digitalisasi Monitoring Proyek dan Absensi Lapangan - Revan Anthony; Marshanda Anabella; Muhammad Iyad Irviansyah; Muhammad Rifqo Saputra; Muhammad Jafni Abbas (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
PT Putra Perwira Abadi is a construction services company facing operational challenges in project monitoring, progress documentation, field attendance, and project data integration. Progress updates are still carried out manually through photos and informal communication, while field attendance has not been able to automatically validate location and time. This study aims to design an Enterprise Architecture using TOGAF ADM to support the digitalization of project monitoring and field attendance. A qualitative approach with a case study method was used, with data collected through semi-structured interviews and literature review. The TOGAF ADM phases applied cover Preliminary Phase through Architecture Change Management. The study produces an architectural design that integrates project monitoring, field attendance, documentation, project finance, and management dashboard. The main proposed solutions include a Project Monitoring System, a geo-tagged photo-based Field Attendance System, a Document Management System, Project Finance Integration, and a Management Dashboard. A Requirements Traceability Matrix (RTM) is used to ensure traceability between problems, architectural requirements, proposed solutions, and success indicators.